VARIASI AGREGAT PIPIH SEBAGAI AGREGAT KASAR TERHADAP KARAKTERISTIK LAPISAN ASPAL BETON (LASTON) - Agus Ariawan, I Made (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 1 Januari 2011)
Laston is a mixture of continuously graded aggregates and asphalt as a binder. Based on its form, the used aggregate is classified as spherical, cube, oval, flaky and irregular. A flaky aggregate is unfavorable to be used as Laston ingredient, because it is broken easily that could affect gradation of aggregate and the interlocking is weak. Therefore, the Determination of Flekiness indexs BS.812 limits aggregate index flaky in the Laston for a maximum of 25%. Research is carried out to study how the effect of flaky aggregate as coarse aggregate on the characteristic of Laston mixture where the Flaky Aggregate used are varied namely 0%, 15%, 20%, 25%, 30%, 35% of the total aggregate. By using 6.25% of KAO, the characteristics of the Laston are as follows. Decreases in the value of stability from 1144 kg to 1096.9 kg, the value of MQ from 313.21 kg/mm to 150.52 kg/mm, the value of VMA from 16.48% to 13.68%, and the value of VIM from 5.90% to 2.73%, increases in the flow from 3.65 mm to 7.21 mm, and the value of VFB from 64.2% to 80.1% are obtained. Based on regression and correlation analyses, the addition of flaky aggregate strongly affects the value of the Laston characteristic. The correlation values (r) of each characteristic are greater than 0.97. Based on the analysis of variance, the value of F count for each Laston characteristic is greater than F table of 3.11 with an error rate ( ) of 5%, the degree of freedom treatment v1 = 5 and degrees of freedom random v2 = 12. This proves that by varying the level of flaky aggregate makes the difference in the values of the Laston mixture characteristics.
Keywords: Laston, Flaky aggregates, Characteristics of Mixed Laston